2017
DOI: 10.3390/ma10070805
|View full text |Cite
|
Sign up to set email alerts
|

Wear Performance of Calcium Carbonate-Containing Knee Spacers

Abstract: Articulating spacers should be wear-resistant and load-bearing to avoid prolonged immobilization of the patient and to reduce morbidity. However, due to the articulation of both components, a release of cement wear particles is to be expected. The aim of this study was to investigate the wear performance of a new spacer cement that contains calcium carbonate as a radio-opaque substance, in comparison to an established barium sulphate-containing spacer material, and also to characterize the amount, morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The silicone mold material is soft and deformation of the cement during polymerization may occur (cement volume will expand but the mold was not strong enough to resist the expansion, so an irregular cement surface was then produced as shown in Figure 4 ). The wear test revealed acceptable results when comparing with the reported data in previous publication [ 24 ], even though the surface condition of the cement region was not ideal. However, the additional mechanical machining would not be recommended due to difficulty in clinical practice.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The silicone mold material is soft and deformation of the cement during polymerization may occur (cement volume will expand but the mold was not strong enough to resist the expansion, so an irregular cement surface was then produced as shown in Figure 4 ). The wear test revealed acceptable results when comparing with the reported data in previous publication [ 24 ], even though the surface condition of the cement region was not ideal. However, the additional mechanical machining would not be recommended due to difficulty in clinical practice.…”
Section: Discussionsupporting
confidence: 58%
“…Elke and Rieker [ 41 ] reported that the estimated threshold for osteolysis-free volumetric wear is around 670 mm 3 . According to the wear testing results in the current study, the dry weight loss of the polyethylene-based spacers was less than that of the commercial cement spacers (Femur: 34.34 mg vs. 149.6 mg; Tibial: 18.78 mg vs. 226.0 mg) [ 24 ]. The volumetric wear of the novel spacer set in the current study, by calculating the average wear volume by loss of dry weight and density of the UHMWPE material (ρ = around 0.95 mg/mm 3 ), was only 55.92 mm 3 , lower than the reported osteolysis-free volumetric wear threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spacers are a temporary treatment option for periprosthetic infection in two stage revision arthroplasty procedures and are normally loaded with antibiotics. , In the Copal Spacem (Heraeus Medical GmbH, Wehreim, Germany) articulating bone cement spacers, CaCO 3 (15 wt %) is used as a contrast agent . Articulating spacers anticipate the release of cement particles during sliding; thus, CaCO 3 is preferred over BaSO 4 because it is nontoxic and less hazardous in the body than Ba 2+ particles. , Furthermore, as CaCO 3 particles are soft and less abrasive, third body-induced wear is reduced. Müller et al observed a 64% reduction in wear in a CaCO 3 -containing spacer compared to a BaSO 4 -containing spacer from the same manufacturer.…”
Section: Resultsmentioning
confidence: 99%